Adult outcomes of sustained high‐quality early child care and education: Do they vary by family income?. Issue 2 (18th October 2021) - Bustamante, Andres S.; Dearing, Eric; Zachrisson, Henrik Daae; Vandell, Deborah Lowe
Abstract: Experimental research demonstrates sustained high‐quality early care and education (ECE) can mitigate the consequences of poverty into adulthood. However, the long‐term effects of community‐based ECE are less known. Using the 1991 NICHD Study of Early Child Care and Youth Development ( n = 994; 49.7% female; 73.6% White, 10.6% African American, 5.6% Latino, 10.2% Other), results show that ECE was associated with reduced disparities between low‐ and higher‐income children's educational attainment and wages at age 26. Disparities in college graduation were reduced the more months that low‐income children spent in ECE ( d = .19). For wages, disparities were reduced when children from low‐income families attended sustained high ‐ quality ECE ( d = .19). Findings suggest that community‐based ECE is linked to meaningful educational and life outcomes, and sustained high‐quality ECE is particularly important for children from lower‐income backgrounds.